Influence of Spacing, Nipping and Fruit Retention on Seed Yield and Seed Quality in Cucumber* - RAVIKUMAR G.H; SHEKHAR GOUDA M; VASUDEVAN; N. BASAVEGOWDA; MAHADEVAREDDY (Seed Research, 2026)
An experiment on seed production in cucumber conducted during kharif indicated that closer spacing of 1.50m x 0.50m (S.) recorded higher fruit yield (154.9 q ha), seed setting (84.1%) and seed yield (76.6 kg ha") though lower in fruit length (18.9 cm) and diameter (19.7 cm) as compared to wider spacing 1.50 x 0.75m (S,). Unnipped (no nipping) treatment recorded higher number of filled seeds per fruit (115.6 fruit), seed extraction (0.54%) seed setting per cent (81.9%) resulting in more seed yield (71.4 kg ha¹) compared to nipping at 12th node (67.3 kg ha¹) and spraying of CCC @ 100 ppm at 40 DAS (64.2 kg ha). Retention of four fruits per vine (F₂), recorded corded significantly higher numbers nun of fille filled seeds per fruit (122.2 fruit’) seed setting percentage (83%) and seed yield (70 kg ha¹) compared to retention of 2 fruits per vine (F,). During summer similar trend was also observed, but the yield levels were relativity lower than kharif. The data clearly indicated that seed yield (86.5 kg ha’), seed quality and benefit cost ratio were higher (2.92) in kharif by adopting narrow spacing, no nipping and retention of four fruits per vine (S,N,F,).